Paclitaxel Modulates the Proliferation and Differentiation of THP-1 Cells Exposed to Inactivated SARS-CoV-2 Virus - Everaldo Hertz; Bárbara Osmarin Turra; Nathália Cardoso de Afonso Bonotto; Fernanda dos Santos Trombini; João Arthur Bittencourt Zimmermann; Cibele Ferreira Teixeira; Verônica Farina Azzolin; Ivo Emilio da Cruz Jung; Ivana Beatrice Mânica da Cruz; Fernanda Barbisan (Revista Brasileira de Cancerologia)
Introduction: Cancer patients were considered a high-risk group for COVID-19. Studies indicate that certain types of cancer, as breast cancer, may exhibit distinct immunological responses. Evidence suggests that paclitaxel (PTX), a chemotherapeutic agent widely used in the treatment of breast cancer, has immunomodulatory properties, which could contribute to attenuate the inflammatory response caused by the SARS-CoV-2 virus. Objective: To evaluate the effect of PTX on the THP-1 immune cell line activated by non-viral immunogenic agent 12-O-tetradecanoylphorbol-13-acetate (TPA) and by inactivated SARS-CoV-2 virus derived from the CoronaVac vaccine (CVac). Method: An in vitro study was conducted, initially determining the minimum concentration of CVac required to activate THP-1 cells. Subsequently, the cytotoxic action of PTX on THP-1 cells was investigated, followed by the analysis of the immunomodulatory effect of PTX through the evaluation of cell proliferation rate, cytomorphological differentiation, levels of nitric oxide, superoxide anion, and gene expression of the cytokines tumor necrosis factor-alpha and interleukin 10. Results: In 24-hour, 5% CVac activated THP-1 cells, triggering more significant proliferation and cell differentiation, compared to the control. No cytotoxic effects of PTX were observed. PTX reduced the cell differentiation rate and superoxide levels when co-exposed with TPA or CVac, but did not modulate cytokine gene expression. Conclusion: The data indicate that PTX could modulate in vitro immune activation in response to viral and non-viral immunogenic agents, suggesting that it could attenuate the inflammatory response to antigens, including SARS-CoV-2.